ANALISIS DAN PERANCANGAN SISTEM PAKAR DIAGNOSA PENYAKIT TANAMAN SAWIT PADA PT. ANDALAN ALAM SUMATRA MENGGUNAKAN METODE FORWARD CHAINING - Kurniawansyah, Kevin; Assegaff, Setiawan (Jurnal Manajemen Sistem Informasi, 2019)
Palm oil is one of the plantations that are often attacked by disease. The disease of this planting plants is spread rapidly, so it must be in the culprit. To know the oil palm plant disease or not to be diagnosed to the symptoms found in the field. At PT Andalan Alam Sumatra there are still many obstacles in peroses diagnosis of oil palm disease, while the constraint that occurs is the lack of knowledge of employees of palm oil disease, still need help from plantation managers in diagnosing disease. Peroses diagnostics will be hampered when plantation managers are not in place or being out of service, this also greatly burden the work of a planter manager. Because of peroses peroses diagnosis of palm oil disease disease peroses disease prevention also become obstructed. As a result, palm oil disease spreads and disrupts the productivity of oil palms, causing death in palm oil. Therefore it is necessary media that can help overcome this as for medianya system of plant disease diagnosis by applying Forward Chaining method. This expert system of plant disease diagnosis using object-based modeling techniques to describe the analysis and system design, namely in the form of use case diagrams, class diagrams, and activity diagrams. The output of this research is the design of prototype system Analysis And Design Expert System Diagnosis Disease Palm Plant At PT. Andalan Alam Sumatra With Forward Chaining Method